THE RESISTANCE OF CORN SELF-POLLINATED LINES AND HYBRIDS TO MAJOR DISEASES AND PESTS IN THE CONDITIONS OF THE RIGHT-BANK FOREST-STEPPE OF UKRAINE - Kolisnyk, O. M. (Scientific Progress & Innovations, 2019)
The purpose of the work was to study and identify self-pollinated lines for the resistance to major diseases and pests, to identify the determinants for developing the principles of selecting parental pairs in creating corn hybrids resistant to the complex of entomo- and phyto-pathogens adapted to the conditions of the Forest- Steppe of the Right-Bank Ukraine. The results of the gradation grouping show that among the selfpollinated corn lines of the collection 28.0 % had high, 50.0 % - average and 22.0 % - low yields, while 10.5 % of simple hybrids belonged to the group with high yields, 54.6 % - to the average, and 34.9 % - to low-yielding. Taking into account that among these 10.5 % hybrid combinations with the yields above 5.5 t/ ha, hybrid combinations with complex resistance to diseases and pests are present on the basis of sin-gled out by us self-pollinated donor lines resistant to entomo- and phyto-pathogens, confirms the principles formulated by us as to selecting parental pairs. Simple hybrids based on such valuable donors of complex resistance to pests and diseases, as УХ 405, МА 22, УХК 409, СМ 5-1-1, F 502 belong to the group of high-yielding. The most uniform distribution was recorded as to damaging by the corn moth, a high resistance to which 42.0 % of self-pollinated lines and 29.1 % of simple hybrids were characterized. A large number of self-pollinated lines had high resistance to corn smut (80.0 %) and flying smut (54.0 %). There were fewer highly resistant simple hybrid combinations to these diseases: 45.3 and 43.0 %, respectively. Thus, in order to obtain hybrids resistant to corn moth, it is necessary to choose both parental forms resistant to this pest, as evidenced by rather close correlation and the results of our previous analysis. As to inheriting the re-sistance to the corn moth damage, a strong link between the hybrids and the two parent forms (r = 0.890; 0.874) is observed, which also requires the selection of both parental forms highly resistant to damage by the above mentioned pest to obtain the identical hybrid progeny. The determined sources of stability conducted by correlation analysis confirmed their general effectiveness in hybrid combinations. The outlined self-pollinated lines that are considered to be valuable and promising as to their further using in breeding prac-tice to create entomo- and phyto-pathogen resistant hybrids are recommended for future studying and using. The conducted research has become the basis for developing practical recommendations and improving the method of determining the resistance of corn plants to pathogens of flying and corn smut.